Users' guides to the medical literature essentials of evidence-based clinical practice - Guyatt, Gordon 1953-; Meade, Maureen O.; Cook, Deborah J. (JAMAevidence, 2015)
"The streamlined companion to the classic Users' guides to the medical literature...fully updated and revised. This compact guide condenses the most clinically relevant content of the landmark Users' Guides to the Medical Literature to help you incorporate evidence-based medicine into your practice. You will learn the principles of evidence-based medicine, how your practice can benefit from the constant stream of new medical literature, and how to differentiate good medical evidence from bad. This edition includes several new chapters and a new emphasis on the role of patient preferences and preappraised resources....Provided by publisher